Optimization of Travelling Water Screen (TWS) Components Replacement in Cooling Water System (Case Study on PLTGU Muara Tawar Blok 1) - Arief Wicaksono; Abdullah Shahab (Institut Teknologi Sepuluh Nopember, 2019)
Traveling Water Screen (TWS) in cooling water system is one of the main cooling equipment of a Combined Cycle Gas Turbine (CCGT) generator, which has a considerable impact towards the steam turbine’s power output and thermal efficiency of the generator in general. This research aims to understand the distribution of TWS component failure which occurs in the filtration process of the cooling water system under the current operating condition, and operational expenditures correlated with it. The analysis started with the collection of TWS maintenance data between 2003 to 2017. Then, the distribution of failure is characterized by using available statistical software. Mathematical models were used to determine optimum replacement policy for each component, based on failure distribution data and replacement/maintenance cost. The optimum replacement interval and minimum replacement cost varies between TWS components. The optimum replacement intervals for each component are as follows: 43.4245 days for bearing bushing; 19.9785 days for bolt, sock head M.16; 40.9505 days for bolt, sock head M.12; 27.6088 days for rubber seal; 48.4359 days for pin, straight plain, 25.4 mm; 88.4978 days for ram, wiremesh; 69.471 days for pin, straight plain, 27/30 mm; and 29.2394 days for nut, hex M.8. The minimum replacement costs for each component are as follows: Rp4,383,400/day for bearing bushing; Rp5,706,850/day for bolt, sock head M.16; Rp12,671,400/day for bolt, sock head M.12; Rp7,247,630/day for rubber seal; Rp6,308,610/day for pin, straight plain, 25.4 mm; Rp5,522,590/day for ram, wiremesh; Rp5,032,190/day for pin, straight plain, 27/30 mm; and Rp4,770,530/day for nut, hex M.8. These findings were further integrated into the implementation of optimum maintenance strategy, especially for stock control, manpower resources smoothing, and maintenance expenditure planning in order to keep the performance of the generator